Plundered skulls and stolen spirits: inside the fight to reclaim native America's culture - Colwell, Chip (The University of Chicago Press, 2017)
Introduction -- Resistance: war gods -- Only after night fall -- Keepers of the sky -- Magic relief -- Tribal resolution -- All things will eat themselves up -- This far away -- Regret: a scalp from Sand Creek -- I have come to kill Indians -- The Bones Bill -- We are going back home -- Indian trophies -- Ac.35b -- A wound of the soul -- Reluctance: killer whale flotilla robe -- Masterless things -- Chief Shakes -- Johnson v. Chilkat Indian Village -- Cranes' last stand -- The weight was heavy -- Our culture is not dying -- Respect: Calusa skulls -- The hardest cases -- Long since completely disappeared -- Unidentifiable -- Their place of understanding -- Timeless limbo -- Before we just gave up -- Conclusion